1999
DOI: 10.1037/0894-4105.13.4.546
|View full text |Cite
|
Sign up to set email alerts
|

Depression in multiple sclerosis: Relationship to working memory capacity.

Abstract: Recent research has shown that depression in multiple sclerosis (MS) is associated with deficits on cognitively demanding tasks. One explanation for this relationship is that depressed MS patients may have reduced working memory capacity. The present study was designed to test this hypothesis. Depressed MS patients were compared with nondepressed MS patients and nondepressed healthy controls on a task of working memory capacity (reading span) and a short-term memory task not taxing working memory capacity (wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
109
4
23

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(145 citation statements)
references
References 37 publications
9
109
4
23
Order By: Relevance
“…Tests that emphasized episodic memory and processing speed were most sensitive and logistic regression models revealed that tests emphasizing processing speed, verbal memory, and executive function were predictive of vocational status. Depression, was not significantly related to cognitive performance, consistent with some previous findings (Benedict et al, 2002a) but not others (Arnett et al, 1999;Arnett et al, 2002). Patients were gleaned from a number of different sources as documented prior to testing.…”
Section: Introductionsupporting
confidence: 84%
See 1 more Smart Citation
“…Tests that emphasized episodic memory and processing speed were most sensitive and logistic regression models revealed that tests emphasizing processing speed, verbal memory, and executive function were predictive of vocational status. Depression, was not significantly related to cognitive performance, consistent with some previous findings (Benedict et al, 2002a) but not others (Arnett et al, 1999;Arnett et al, 2002). Patients were gleaned from a number of different sources as documented prior to testing.…”
Section: Introductionsupporting
confidence: 84%
“…In general, correlations between NP testing and depression are modest, sometimes significant (e.g., Arnett et al, 1999;Arnett et al, 2002), sometimes not (e.g., Benedict et al, 2002a). Our analysis provided an opportunity to learn if such variation is related to recruitment context.…”
Section: Discussionmentioning
confidence: 91%
“…The MS literature provides a couple of other studies showing that depressed MS patients performed significantly worse on executive types of cognitive tasks that could be construed as overlapping somewhat in the constructs measured by the IGT. Specifically, Arnett et al reported lower performances in a depressed group of MS patients in comparison to nondepressed MS patients on a planning task [4], and showed the same pattern for a working memory task that is considered executive in nature [3]. Besides, Landro et al [25] reported that depressive symptoms also accounted for slowed information processing speed in MS patients.…”
Section: Discussionmentioning
confidence: 99%
“…We postulated that (1) early MS patients without disability may make more risky choices in the IGT than healthy subjects, (2) MS patients with a higher disease activity, defined by the occurrence of a relapse during an observation period of 15 months after performing the IGT, may be impaired earlier in their ability of decision making than stable patients (i. e., without relapses), (3) "risk-taking" MS patients may finally present different behavioral characteristics, a lower quality of life (QoL), or a higher perceived handicap than "non-risk-taking" MS patients, defined according to their IGT performance.…”
Section: Introductionmentioning
confidence: 99%
“…34,35 The neuropsychologist should always evaluate the patient's psychological functioning and screen for the presence of psychiatric disorders. Sleep disturbance is also common in MS and can contribute to fatigue and cognitive inefficiency.…”
Section: Interpretation Of Test Resultsmentioning
confidence: 99%